2016
DOI: 10.9744/ced.18.2.103-108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Precipitation Rate of Calcium Carbonate Produced through Microbial Metabolic Process of Bio Materials

Abstract: Abstract:Concrete is the most widely used construction material in civil engineering. But plain concrete is a brittle material and has little resistance to cracking. The cracking in concrete promotes deterioration such as the corrosion of reinforcing rebar, therefore, repair in filling the crack is often carried out. Recently, repair methods using bio-based materials associated with microbial metabolic processes leading to precipitation of calcium carbonate have been intensively studied. In this study, influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Otherwise, the precipitation rate of the calcium carbonate was slower when the temperature was lower. According to Putri [30], the 20-30 • C range is the optimum temperature range for increasing the precipitation of calcium carbonate.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Otherwise, the precipitation rate of the calcium carbonate was slower when the temperature was lower. According to Putri [30], the 20-30 • C range is the optimum temperature range for increasing the precipitation of calcium carbonate.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…It has been reported that the precipitation rate was largely dependent on the concentration of constituents, pH levels, and ambient environment such as temperature. The effect of temperature is significant in facilitating the precipitation process (Putri et al, 2016), thus leading to a larger amount of precipitates formed compared to those tested in normal room conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Putri, et al [22]- [24] observed precipitation of calcium carbonate caused by metabolic activity of stagnant bio-based material in the test tubes. The precipitates are mainly comprised of calcium carbonate up to 48h after mixed.…”
Section: Introductionmentioning
confidence: 99%